High performance biogranulation technologies for Jurong Island - Tay, Stephen Tiong Lee. (2008)
This project aims to investigate aerobic biogranulation for biological wastewater treatment. To study the effect of high organic loading rate on the aerobic biogranulation process and to characterize and monitor the waste-degrading microorganisms with the aid of advanced molecular microbiology tools.